Yield and quality of a grassland in a grassland in south of Durango, Mexico - Rodríguez-Ortega, Leodan Tadeo; Trejo-Laguna, Eduardo; Nava-Martínez, Daira; Rodríguez-Ortega, Alejandro; Hernández-Guzmán, Filogonio Jesús; Landa-Salgado, Patricia (Ecosistemas y Recursos Agropecuarios, 2025)
Given the need to know the forage yield and proportion of grass species in the malpais area in southern Durango, the objective was to determine the forage yield, dead material, botanical composition and forage quality in autumn 2023 in Rancho El Ojo, municipality of Poanas. The microsites (treatments) were breña, cristón, llano and malpais. A completely randomized design with eight repetitions, ANOVA and Tukey (α = 0.05). The highest yield of forage material was observed in criston (P < 0.05, 8657 kg ha-1) and surpassed breña, llano and malpais by 1.14, 1.06 and 1.07 times, respectively. Dead material contributed 32, 28, 25 and 28% to the yield for each microsite respectively. The grasses that contribute the most value to the yield were Rhynchylytrum repens (39.4%), Bothriochloa saccharoides (17.6%), Bouteloua curtipendula (22.8%), Bouteloua gracilis (4.6%). The highest crude protein content was found in breña (8.7%), as well as total digestible nutrients (55%). The highest percentage of neutral detergent fiber (84.2) and acid detergent fiber was in malpais (57.8). Lignin was more evident in criston (10.2%) and was lower (P < 0.05) in breña (5.0%). The plain forage material showed higher digestibility (49%) as well as non-fibrous carbohydrates (13.2%). The highest metabolic energy occurred in breña (2.0 Mcal ME kg-1) and exceeded cristón, llano and malpais by 1.24, 1.11 and 1.28, respectively. Rancho El Ojo located in southern Durango has been organizing forage material for livestock in a sustainable manner given the forage quantities determined per microsite.